1993
DOI: 10.1111/j.1365-2141.1993.tb03362.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonal chromosomal abnormalities in Fanconi's anaemia: what do they really mean?

Abstract: Summary. Patients with Fanconi's anaemia (FA) have aplastic anaemia, leukaemia, myelodysplasia and tumours. Since leukaemia has a very poor prognosis, it is desirable to identify high‐risk patients. To determine the significance of clonal marrow chromosomal abnormalities we began a prospective study in 17 patients: five were normal, eight aplastic, and four myelodysplastic. Three of 11 with adequate cytogenetics had transient abnormal clones. None had leukaemia at 3–24 months. Changing cytogenetic patterns ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 15 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…[ 34 36 ] Such a delay in identification of FA patients and at-risk families can be avoided by performing the MMC-stress test in patients with macrocytosis and decreased platelet count, as observed during screening of complete blood count with differentials. [ 34 37 ] In a recent report, it is shown that MMC-induced DNA damage also can be used as an index for FA identification. [ 38 ] We suspect a correlation between sensitivity of cells to alkylating agents, measured as breakage index, and the amount of cells containing aberrations, measured as the percentage of aberrant cells.…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 36 ] Such a delay in identification of FA patients and at-risk families can be avoided by performing the MMC-stress test in patients with macrocytosis and decreased platelet count, as observed during screening of complete blood count with differentials. [ 34 37 ] In a recent report, it is shown that MMC-induced DNA damage also can be used as an index for FA identification. [ 38 ] We suspect a correlation between sensitivity of cells to alkylating agents, measured as breakage index, and the amount of cells containing aberrations, measured as the percentage of aberrant cells.…”
Section: Discussionmentioning
confidence: 99%
“…12–14 However, incomplete characterization of the aberrations owing to limitations in available techniques, the absence of the more common recurring abnormalities in AML, the presence of background chromosomal instability generating nonclonal abnormalities, and the occasional report of “transient” clones have raised the issue of the clinical significance of these clonal abnormalities. 14,15 More recently, Tonnies et al 16 have shown that a clone resulting in an extra copy of the distal long arm of chromosome 3 in FA is associated with a poor prognosis. Yet questions remain regarding the spectrum and clinical significance of clonal cytogenetic abnormalities.…”
mentioning
confidence: 99%
“…Therefore, minimal diagnostic criteria for secondary MDS following an underlying IBMFS have been developed [33] (increased BM blast count, development of a hypercellular marrow in the presence of persistent PB cytopenias and acquired clonal chromosomal abnormalities). However, studies in FA and SDS indicate that clonal cytogenetic abnormalities are not universally associated with disease progression and poor outcomes since cytogenetic changes may persist for years without evolution to MDS/ AML [3,4,51].…”
Section: Secondary Mdsmentioning
confidence: 99%